Mycobacterial Dormancy Regulon Protein Rv2623 as a Novel Biomarker for the Diagnosis of Latent and Active Tuberculous Meningitis - Ruchika K. Jain (Disease Markers, 2013)
The present study was designed to investigate Rv2623 antigen, a major dormancy regulon protein of Mycobacterium tuberculosis (MTB) in CSF of suspected latent and active tuberculous meningitis (TBM) patients. A total of 100 CSF samples from TBM (n=31), suspected latent TBM (n=22), and suitable noninfectious control subjects (n=47) were collected and evaluated for Rv2623 antigen level using ELISA protocol. A significantly high (P<0.05) mean absorbance was observed in samples of suspected latent TBM and active TBM patients as compared to non-TBM control patients. However, no significant difference in Rv2623 level was observed between suspected latent TBM and TBM patients. Our preliminary findings suggest that Rv2623 may be useful as a potential biomarker for the diagnosis of the latent as well as active TBM infection. Futher evaluation of this biomarker in large number of samples is therefore needed to confirm the result.